A study of ripple effects in software ecosystems (NIER track) - Robbes, Romain; Lungu, Mircea (2011 33rd International Conference on Software Engineering (ICSE), 2011)
When the Application Programming Interface (API) of a framework or library changes, its clients must be adapted. This change propagation - known as a ripple effect - is a problem that has garnered interest: several approaches have been proposed in the literature to react to these changes. Although studies of ripple effects exist at the single system level, no study has been performed on the actual extent and impact of these API changes in practice, on an entire software ecosystem associated with a community of developers. This paper reports on early results of such an empirical study of API changes that led to ripple effects across an entire ecosystem. Our case study subject is the development community gravitating aroung the Squeak and Pharo software ecosystems: six years of evolution, nearly 3,000 contributors, and close to 2,500 distinct systems.